Response of Mouse Zygotes Treated with Mild Hydrogen Peroxide as a Model to Reveal Novel Mechanisms of Oxidative Stress-Induced Injury in Early Embryos. (22nd September 2016) - Qian, Diting; Li, Zhiling; Zhang, Yuting; Huang, Yue; Wu, Que; Ru, Gaizhen; Chen, Man; Wang, Bin
Abstract : Our study aimed to develop embryo models to evaluate the impact of oxidative stress on embryo development. Mouse zygotes, which stayed at G1 phase, were treated with prepared culture medium (containing 0.00, 0.01, 0.02, 0.03, 0.04, 0.05, or 0.1 mM hydrogen peroxide (H2 O2 )) for 30 min in experiment 1. The dose-effects of H2 O2 on embryo development were investigated via comparisons of the formation rate at each stage (2- and 4-cell embryos and blastocysts). Experiment 2 was carried out to compare behaviors of embryos in a mild oxidative-stressed status (0.03 mM H2 O2 ) with those in a control (0 mM H2 O2 ). Reactive oxygen species (ROS) levels, variation of mitochondrial membrane potential (MMP), expression of γ H2AX, and cell apoptosis rate of blastocyst were detected. We observed a dose-dependent decrease on cleavage and blastocyst rates. Besides, higher level of ROS, rapid reduction of MMP, and the appearance of γ H2AX revealed that embryos are injured early in mild oxidative stress. Additionally, γ H2AX may involve during DNA damage response in early embryos. And the apoptotic rate of blastocyst may significantly increase when DNA damage repair is inadequate. Most importantly, our research provides embryo models to study cell cycle regulation and DNA damage response under condition of different levels of oxidative stress.